Evaluating the Effectiveness of Peer-led Anti-Alcohol Educational Intervention on Reducing Alcohol Use among School Students - Sharma, Bhagawoti; Devkota , Bhimsen (Journal of Health Promotion, 2025)
Alcohol use is a major public health concern worldwide, and school students are vulnerable to alcohol use. School-based interventions aim to prevent or delay the initiation of alcohol use among adolescents. The purpose of the study is to assess the impact of the peer-led anti-alcohol educational intervention on students’ knowledge, perception, and practice related to alcohol use. Using a quasi-experimental (one group; pre, and post-test) design, a non-probability convenience sampling technique was employed to collect a sample of 60 students amongst four classes (9th to 12th) in a selected school. A self-administered questionnaire was used as a tool for collecting pre-test and post-test data. Intervention was developed based on the need assessment results and a review of the literature. The anti-alcohol educational intervention included thirteen sessions, all delivered by peer-educators. Data were analyzed using a paired t-test and the Wilcoxon Signed-Rank Test. The results show that students’ post-test mean knowledge scores (14.55) on alcohol use were significantly (P<0.05) increased from the pre-test score (13.32). Likewise, the student’s post-test mean score (88.75) on perception of alcohol use was significantly (P<0.05) higher than pre-test mean perception scores (88.75). Furthermore, the student’s post-test mean alcohol practice score (2.98) was significantly (P<0.05) decreased compared to the pre-test mean alcohol practice score (5.53). These results indicate that students’ knowledge and perception scores on alcohol use significantly increased after the anti-alcohol educational intervention, indicating a better awareness and more negative attitudes toward alcohol consumption. Meanwhile, their practice scores, which gauged self-reported alcohol use behaviors, significantly decreased, indicating a decline in alcohol-related behaviors. Therefore, the study suggests that integrating peer-led anti-alcohol educational interventions into secondary school education could improve knowledge, and attitudes, and decrease alcohol consumption among students.